2022
DOI: 10.1055/s-0042-1755621
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of COVID-19 on the Orthopaedic Surgery Residency Match

Abstract: Introduction Matching into an orthopaedic surgery residency program presents a challenging accomplishment for applicants to achieve in any given year. Due to the profound changes to the application process caused by the coronavirus disease 2019 (COVID-19) pandemic it was theorized that there would be a change in the number of graduates matching close to their home medical school region, state, and program. Methods Orthopaedic surgery residency program Web sites and social media accounts were accessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Another study found that 39.6% of applicants matched to a program within their state, compared with 33.1% prepandemic, which was a statistically significant difference 36 . A third study also found increased home program matches, at 27.4% compared with 21.2% prepandemic, and home state matches at 37.8% vs. 33.4% prepandemic 37 . Social media also became an important consideration for applicants because 34% of applicants said that social media influenced their rank lists 38 .…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…Another study found that 39.6% of applicants matched to a program within their state, compared with 33.1% prepandemic, which was a statistically significant difference 36 . A third study also found increased home program matches, at 27.4% compared with 21.2% prepandemic, and home state matches at 37.8% vs. 33.4% prepandemic 37 . Social media also became an important consideration for applicants because 34% of applicants said that social media influenced their rank lists 38 .…”
Section: Resultsmentioning
confidence: 85%
“…In addition, PDs will need to consider the biases inherent to a hybrid approach where those selecting virtual option, possibly due to socioeconomic factors, may be graded lower than in-person counterparts due to lack of personability. It is unsurprising given these limitations that orthopaedic surgery residency applicants were more likely to match in the same state or region during the pandemic [35][36][37] .…”
Section: Discussionmentioning
confidence: 99%
“…During this period, orthopaedic away rotations for medical students nationwide were restricted severely or altogether suspended in some locations, thereby limiting opportunities for student interaction with orthopaedic faculty at other residency programs. 7 In this context, our residents proposed establishing an orthopaedic education program to create a framework for medical student mentorship. Undertaken as a quality improvement (QI) project, the goals of this program were to familiarize medical students at our institution with orthopaedics as a potential career choice, to increase student-resident interaction, and to foster and cultivate orthopaedic mentorship.…”
Section: Introductionmentioning
confidence: 99%